Cultural and economic barriers and opportunities for the participation of women in agricultural production systems: A case study in Guatemala - Berrospi, Maria Lucia; Hernandez, Manuel A.; Alarcón, Constanza; Lopera, Diana Carolina; Quintero, Diana; Reyes, Byron A.; Olivet, Francisco (International Food Policy Research Institute, 2023)
Agricultural activities in Guatemala constitute 32% of the total employment, but only one in every 10 individuals employed in these activities are women. This study examines cultural and economic barriers and opportunities for women’s participation in crop and livestock production systems. We used a qualitative approach involving focus groups with 15–20 women in eight communities in Chiquimula and Huehuetenango in 2022. The findings are consistent across locations. First, women seem not to be strongly interested in crop-production activities, except harvesting, and they only get involved in specific tasks. This lack of interest and participation can be related to low empowerment levels and traditional gender stereotypes, and persists even in locations with a high male emigration, where women could be expected to take over traditionally male croprelated tasks. Second, participants perform a variety of unpaid activities (e.g., raising small-scale livestock and maintaining home gardens), which they do not recognize as formal income-generating occupations. Third, women consider commercialization of their products a challenge as they lack access to markets beyond their communities. This also deters applicants from applying for credit due to fear of defaulting. The main aspirations of participants are to generate income from non-crop-related activities, mainly livestock oriented, or to emigrate for better prospects. This study underscores the need to help women not only start new activities, but also provide them with continuous support services in production and commercialization, management, accounting, and financial literacy, as well as building agency through existing women’s organizations and facilitating access to credit.